Inducible T-Cell Costimulator Mediates Lymphocyte/Macrophage Interactions During Liver Repair - Ramavath, Naresh Naik; Gadipudi, Laila Lavanya; Provera, Alessia; Gigliotti, Luca C.; Boggio, Elena; Bozzola, Cristina; Albano, Emanuele; Dianzani, Umberto; Sutti, Salvatore (Frontiers in Immunology, 2021)
The liver capacity to recover from acute liver injury is a critical factor in the development of acute liver failure (ALF) caused by viral infections, ischemia/reperfusion or drug toxicity. Liver healing requires the switching of pro-inflammatory monocyte-derived macrophages(MoMFs) to a reparative phenotype. However, the mechanisms involved are still incompletely characterized. In this study we investigated the contribution of T-lymphocyte/macrophage interaction through the co-stimulatory molecule Inducible T-cell co-stimulator (ICOS; CD278) and its ligand (ICOSL; CD275) in modulating liver repair. The role of ICOS/ICOSL dyad was investigated during the recovery from acute liver damage induced by a single dose of carbon tetrachloride (CCl4). Flow cytometry of non-parenchymal liver cells obtained from CCl4-treated wild-type mice revealed that the recovery from acute liver injury associated with a specific up-regulation of ICOS in CD8+ T-lymphocytes and with an increase in ICOSL expression involving CD11bhigh/F4-80+ hepatic MoMFs. Although ICOS deficiency did not influence the severity of liver damage and the evolution of inflammation, CCl4-treated ICOS knockout (ICOS-/-) mice showed delayed clearance of liver necrosis and increased mortality. These animals were also characterized by a significant reduction of hepatic reparative MoMFs due to an increased rate of cell apoptosis. An impaired liver healing and loss of reparative MoMFs was similarly evident in ICOSL-deficient mice or following CD8+ T-cells ablation in wild-type mice. The loss of reparative MoMFs was prevented by supplementing CCl4-treated ICOS-/- mice with recombinant ICOS (ICOS-Fc) which also stimulated full recovery from liver injury. These data demonstrated that CD8+ T-lymphocytes play a key role in supporting the survival of reparative MoMFs during liver healing trough ICOS/ICOSL-mediated signaling. These observations open the possibility of targeting ICOS/ICOSL dyad as a novel tool for promoting efficient healing following acute liver injury.